DEVELOPMENT OF PESTICIDE-LOADED NANOPARTICLES FOR CONTROLLED AND TARGETED CROP PROTECTION (Journal of Medical & Health Sciences Review, 2025)
The development of pesticide-loaded nanoparticles represents a promising advancement in sustainable agriculture, offering controlled and targeted crop protection while minimizing environmental harm. This study focuses on synthesizing and characterizing chitosan-based nanoparticles loaded with imidacloprid, using the ionic gelation method to achieve high encapsulation efficiency (78–85%) and loading capacity (12–15%). Dynamic Light Scattering (DLS) revealed uniform nanoparticle sizes (180–220 nm) and a high zeta potential (+35 mV), ensuring colloidal stability and effective interaction with negatively charged pest membranes. Scanning Electron Microscopy (SEM) confirmed spherical morphology and smooth surfaces, while FTIR analysis demonstrated successful pesticide incorporation through hydrogen bonding and ionic interactions.The nanoparticles exhibited a biphasic release profile, with an initial burst release (30% within 12 hours) followed by sustained release over 5–7 days, aligning with the Higuchi model. Bioassays against Helicoverpa armigera showed 90% mortality within 48 hours, outperforming conventional pesticides (70% mortality) without phytotoxicity. Environmental assessments highlighted reduced pesticide leaching, with over 60% retention in topsoil, and significantly lower toxicity to non-target organisms (e.g.,